تأثير بعض العوامل الإحيائية والكيميائية في مكافحة حشرة حفار أوراق الطماطة Tuta absoluta (Meyrick, 1917) (Lepidopte/The effect of some biological and chemical agent to control the Tomato Leaf Miner Tuta absoluta (Meyrick, 1917) (Lepidoptera : Gelechiidae) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
This study was conducted for the period from 10 \ 10 \ 2015 to 01/06/2016 in the College of Agriculture/AL-Qasim Green University for to study the influence of some biological and chemical control to control the Tomato Leaf Miner Tuta absoluta. Highest Adults density calculated by using Pheromone traps has densities peaked at the beginning of April, with 98.4 adults\ trap and then began to decline to the end of May, it was 22.5 adult \ trap.Also the biological control and chemical tests in laboratory referred to the superiority of the chemical pesticide Prochlaim , bio-pesticide Spinosad and extract Neem Oil in mortality ratio reaching 88.77, 84.26 and 83.73% respectively. The lowest mortality ratio was in growth regulator  Admeral , which amounted to 17.00%. So as the length of time treatment a significant effect after 15 days of treatment reached the highest mortality ratio was 77.45% compared to the other days.As for the extract of Citrullus colocynthis in three concentrations and fungus Trichoderma harzianum it was less effective compared with other treatments, and a mortality ratio of the loss of larvae was after 15 days after the spraying process as it was (87.00, 74.00, 64.67 and 63.67)% for each of the C. colocynthis extract 1.8 , C. colocynthis extract 1.2, T. harzianum  and C. colocynthis extract 0.6 respectively.